"Nothing should jiggle while you're moving": Preparing the fat body for an American "plus-size" pageant. Issue 3 (2nd September 2022) - Prohaska, Ariane
ABSTRACT: There is limited scholarly information about beauty pageants for fat women. Based on a larger study about how pageant participants define beauty and health, this paper examines the presentation of fat bodies in a plus-size beauty pageant, and how the pageant constructs, rewards, and reinforces specific types of fat performativity. Although the plus-size pageant is challenging traditional ideas of beauty in terms of body size, pageant participants are expected to be "good fatties". The pageant teaches competitors the socially acceptable ways to eat and to dress for one's body. Pageant competitors are taught that looking beautiful means to "discipline their corpulence", while the pageant simultaneously delivers the messages of "big is beautiful" and that beauty comes from within. The paper concludes with implications of these findings on gender and femininity, and fat studies, and fashion studies scholarship.